Learning Psychological Overview of Kitab Kuning Teaching Learning (Study on Pondok Pesantren Al-Is’af Kalabaan Guluk-Guluk Madura) - Solichin, Muchlis; Effendy, Moh Hafid (TADRIS: Jurnal Pendidikan Islam, 2020)
Pesantren (Islamic boarding school) is the traditional Islamic educational institution. Kiai as the leader of pesantren has an authority in managing, choosing the education system, curriculum (manhaj) that will be used, and also kinds of text books that will be used in teaching and learning process.  Generally, Kiai uses Kitab Kuning (KK, yellow books) also called classical Islamic books, as the material of teaching-learning in pesantren. This paper aims at examining teaching-learning of KK in pesantren. The research method of the study is qualitative . The results of the reseach are that 1) there are levels of learning material KK in line with cognitive development, 2) the pesantren applied the prerequisite knowledge, 3) the pesantren applied the methods of teaching learning, 4) the pesantren applied the tutorial of KK teaching learning.